ALGORITMA RAY-TRACING DALAM 3D FOTOREALISTIK RENDERING UNTUK VISUALISASI OBJEK DUNIA NYATA - Oka Rosalin, Agnes; Lusiana, Veronica (Information Technology and Telematics, 2018)
Abstract – Digital image engineering is progressing to the limits of realism that looks perfect. To form a realistic graphic image, so that it reflects the real reality, 3D modeling and photorealistic rendering techniques are used. The purpose of this study is to create realistic graphic images to visualize real-world objects in the form of 3-dimensional images. From making this graphic image, aspects that support 3D modeling will be analyzed so that they look real, and analyze the ray-tracing algorithm when used to process the 3D model into a graphic image. Ray-tracing is a rendering technique that calculates scene images by simulating the way light rays travel in the real world. The process of making graphic images is related to the study of geometry, surface characteristics and lighting. The methodology in making this graphic image uses the MDLC methodology.